(untitled) (IJOVTECH, 2026)
Microfinance institutions (MFIs) are becoming key tools in ensuring economic stability among the low-income earners in the developing parts of the world especially in agrarian economies such as Ebonyi State, Nigeria. The present work examines the importance of MFIs to economic resilience due to access to credit, savings mobilization, and financial education based on the primary data collected among 300 of the beneficiaries in Ebonyi State. The research uses a survey-based methodology because it involves the use of descriptive statistics and regression analysis to determine the effects on income, savings, and resilience scores. These discoveries indicate that MFIs play an important role in income growth as average monthly income increased by N336,878 on average to N618,706 on average after MFI participation which was N281,828 before MFI participation. The savings made a significant improvement, which was between N51,265 and N289,785. The demographic data indicate that the participants are mainly female (54.7 percent) who have an average age of 39.4 years and are involved in farming (37 percent) and trading (29.7 percent). It combines the theory of economic resilience (based on adaptive capacity to shocks) and the microfinance concept of financial inclusion. The regressions find that years of MFIs and loan sums have a positive impact on resilience, but only at p <0.05, which implies that such contextual characteristics as a lack of infrastructure moderates the impacts. The paper identifies the capabilities of MFIs to reduce poverty and achieve economic stability in Ebonyi State, which is a relatively poor state and susceptible to market and climate shock. Policy suggestions are policy improvements to the outreach and integration of the MFI with agricultural support programs. The study has a contribution of value to the body of literature in the sense that it contains an empirical evidence of a relatively underrepresented state in Nigeria, and incorporates both the old and the new view on the developmental role of microfinance